Legal Vacuum in Regulating the Status of Refugees and Asylum Seekers in Indonesia as a Consequence of Non-Ratification of the 1951 Convention and the 1967 Protocol - Ratna Pristiana Mulya; Rineke Sara (Yayasan Cendekia Gagayunan Indonesia, 2025)
There is a legal void concerning the status of refugees and asylum seekers because Indonesia has not yet joined the 1951 Convention on the Status of Refugees and its 1967 Protocol. Current national laws, especially Presidential Regulation No. 125 of 2016, provide only technical guidelines for administrative matters, such as shelter and inter-agency coordination, without regulating the substantive legal status or basic rights of refugees. This situation results in the absence of a national mechanism for determining refugee status and complete dependence on the United Nations High Commissioner for Refugees (UNHCR), ultimately weakening Indonesia's legal sovereignty. From a social, political, and economic perspective, the presence of refugees creates additional burdens for local governments, potential conflict with local communities, and challenges in international diplomacy, particularly with the refugees' final destination countries. Human rights aspects are also affected, as refugees often lack adequate access to education, health care, and employment, increasing their vulnerability. This article emphasizes the importance of normative steps such as ratifying the 1951 Convention and the 1967 Protocol, drafting specific legislation regarding refugees, improving inter-agency cooperation by working with global institutions like the International Organization for Migration (IOM) and the UNHCR. A human rights-based policy approach that consistently considers national security interests is a solution that can balance humanitarian moral obligations with state sovereignty. In this way, Indonesia is expected to be able to provide more comprehensive protection for refugees while maintaining its international reputation